Isolasi dan Identifikasi Bakteri pada Sayuran Bayam yang Diperjualbelikan Di sekitar jalan Nuri Baru Kota Makassar - Andi Auliyah Warsyidah (Jurnal Media Laboran, 2017)
The purpose of this research is to know the result of Isolation and Identification of bacteria on spinach vegetables sold around Nuri Baru Street of Makassar City and also to determine the bacteria contained in spinach vegetables, this type of research is descriptive research and describe as clear as possible and is observational laboratory. Sampling is done by purposive sampling technique. The population in this research is all spinach vegetables traders around Nuri Baru Street of Makassar City. The results showed that from 2 samples under study where the first sample with the code A found the bacteria Enterobacter cloacae and the second sample with the code B there is bacteria Citrobacter diversus on spinach vegetables traded in the vicinity of the New Nuri Makassar